Short dental implants in microvascular free flap DCIA: A case report - Barbora Hocková; Rastislav Slávik; Basel Azar; Jakub Stebel; Dušan Poruban; Estevam A. Bonfante; Rolf Ewers; Adam Stebel (Heliyon, 2024)
Placing dental implants in microvascular bone free flaps used for reconstructing the mandible or maxilla has been previously reported. However, there is scarce information available on the restorative protocol using short dental implants placed in a deep circumflex iliac artery (DCIA) microvascular free flap and the rationale behind it. This case report describes a 18-year-old patient referred to the hospital for numbness and dull pain of the left mandible, which she observed for three months. The patient underwent mandible resection and reconstruction using the DCIA free flap due to “giant cell lesion” on the left side of the mandibular angle. Short dental implants were placed and prosthetic reconstruction of the dentition involved in the resection was performed in a young patient with two integrated abutment crowns. The placement of short dental implants did not negatively affect the vascular pedicle and vitality of free flap. In our case report, two years after the healing, excellent aesthetic and function were accomplished with the DCIA flap followed by restoration with short implants.